2013
DOI: 10.2527/jas.2012-6007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of castration and dehorning in series or concurrent castration and dehorning procedures on stress responses and production in Holstein calves1

Abstract: The study objective was to compare serum cortisol as an acute stress measure, chute exit velocity as a behavioral measure, and ADG as an indicator of performance and well-being after castration, dehorning, or concurrent castration/dehorning of calves when performed in parallel and in series. Intact male Holstein calves, 3 to 4 mo, underwent sham handling before 2 procedures performed in series separated by 2 to 3 wk. In Period 1, calves were either dehorned by amputation, surgically castrated, concurrently cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
3
7
1
2
Order By: Relevance
“…For example, Ballou et al (2013) and Sutherland et al (2013) observed an increase in plasma cortisol concentrations when castration and dehorning were combined compared with when they were done alone, and the behavioural responses were elevated by combining both procedures . In contrast, Mosher et al (2013) did not find differences in plasma cortisol, when castration was performed alone or concurrently with dehorning; however, in this study, calves were acclimated by sham castration and sham dehorning the day before. To date, no published studies have evaluated the combination of castration and branding or their long-term effects (lasting more than 7 d post procedure) on indicators of pain, inflammation, or wound healing when the two procedures are combined.…”
Section: Introductioncontrasting
confidence: 83%
See 1 more Smart Citation
“…For example, Ballou et al (2013) and Sutherland et al (2013) observed an increase in plasma cortisol concentrations when castration and dehorning were combined compared with when they were done alone, and the behavioural responses were elevated by combining both procedures . In contrast, Mosher et al (2013) did not find differences in plasma cortisol, when castration was performed alone or concurrently with dehorning; however, in this study, calves were acclimated by sham castration and sham dehorning the day before. To date, no published studies have evaluated the combination of castration and branding or their long-term effects (lasting more than 7 d post procedure) on indicators of pain, inflammation, or wound healing when the two procedures are combined.…”
Section: Introductioncontrasting
confidence: 83%
“…Castration is typically performed in conjunction with other painful procedures such as dehorning, branding, and vaccination. To date, all published studies evaluating the combined effect of two painful routine management procedures have assessed castration in combination with dehorning (Schwartzkopf-Genswein et al 2005;Ballou et al 2013;Mosher et al 2013;Sutherland et al 2013). Hot-iron branding is a method used to permanently identify cattle, and it is still commonly used in countries where no electronic identification is required or in areas where producers comingle animals on community pastures.…”
Section: Introductionmentioning
confidence: 99%
“…Weight loss was greatest in CONN calves and lowest in CONP calves. This aligns with previous findings showing concurrent castration and dehorning to negatively impact average daily gain (ADG) [23,27]. Weight change of BMTA calves did not differ significantly from that of CONP calves, indicating that a combination of TA and MEL may provide superior pain relief than TA or MEL alone.…”
Section: Discussionsupporting
confidence: 89%
“…For example, increased nociceptor activity increases sympathetic tone and adrenal secretions, potentially inhibiting gastric control centres, causing decreased rumen motility [26]. A reduction in weight gain is expected to follow castration and dehorning [27], suggesting poor animal welfare and economic losses result from such procedures [24]. In the current study, all calves, including CONP calves, appeared to lose weight over the 6 days following treatment.…”
Section: Discussionmentioning
confidence: 63%
“…Por otra parte, el posicionamiento de la temática del bienestar animal y su impacto tanto en la producción como en la calidad del producto obtenido ha cobrado mayor rele-vancia durante la última década (Müller-Lindenlauf et al, 2010). Sin embargo, también ha cuestionado algunas prácticas habituales de manejo animal tales como inyecciones, descuerne y castración (Mosher et al, 2013). En este sentido, Hocquette et al (2014) han asociado a la castración como uno de los factores extrínsecos que afectan la calidad de la carne.…”
Section: Introductionunclassified